GENETIC VARIABILITY OF HALF SIBS EUCALYPTUS PROGENIES FOR COLD TOLERANCE - Moraes, Cristiano Bueno de; Carvalho, Edmar Vinicius de; Zimback, Leo; Limeira Luz, Otavio dos Santos; Pieroni, Gustavo Bloise; Mori, Edson Seizo [UNESP]; Alves de Barros Leal, Tarcisio Castro (Univ Federal Vicosa, 2015)
The aim of this study was to estimate quantitative genetic parameters of progenies under frost situations and to determine the interaction of genotype x environments for Eucalyptus dunnii progenies in two different sites. The progeny trials were set up in 2010, using 20 open pollination progenies of E. dunnii. The following variables were evaluated: plant height (HGT), diameter at breast height (DBH), and wood volume (VOL) in cubic meters. Descriptive and statistical analysis were used as well as phenotypic/genotype correlation by location and joint variance analysis and the genetic parameters were estimated. Significant differences were detected (p< 0,05) among progenies for silvicultural characters, suggesting the possibilities for selection gain. By the joint analysis, the interaction of progenies x environments (P x E) did not show significant differences, confirming that the superior progenies identified in the tests can be used for both studied locations. The genetic and phenotypic correlations results ranged from low to high (0.23 to 1.0) values for the studied characters, and the great majority of correlations were significant (p< 0,05) in which the diameter at breast height was highly correlated with volume. Because of high genetic variability and genetic control of the characters, the population allows to obtain gains with selection between in the progenies.
Keywords: Eucalyptus dunnii; Forest breeding; Frost